Influence of extraction technique on nutrient content, antioxidant and antimicrobial activity of aqueous extracts of commercial apricot kernels - HoroziÄ‡, Emir; SuljagiÄ‡, Jasmin; GojkoviÄ‡, Jasna; HalilÄeviÄ‡, Eldin; KubiÄek, Darja; CiloviÄ‡ KazareviÄ‡, Ermina (International Journal of Advanced Chemistry, 2020)
This paper presents the results of influence of extraction technique on phytochemical composition and biological activity of aqueous extracts of commercial apricot kernels. Three techniques were used for extraction: maceration, ultrasonic and Soxhlet extraction. The content of total phenols, flavonoids, bioelements, antioxidant and antimicrobial activity was analyzed in the extracts. Antioxidant activity was analyzed in vitro using DPPH and FRAP methods. Antimicrobial screening was performed by diffusion technique on reference strains from the ATCC collection. The content of total phenols and flavonoids is highest in extracts obtained by ultrasonic extraction and maceration. These techniques have proven to be the best for the extraction of macro and micronutrients. The aqueous extract obtained by maceration at 300 rpm for 3 hours showed a greater inhibitory effect against the tested microorganisms, compared to the extracts obtained by other techniques. The least efficient method of extracting bioactive components from apricot kernels is Soxhlet extraction, with the lowest dry extract yield of 5.5%.Â Â Â